Globalization and the Challenges of Public Administration Governance, Human Resources Management, Leadership, Ethics, E-Governance and Sustainability in the 21st Century - Khan, Haroon A. (Springer International Publishing, 2018)
This book is an attempt to understand the challenges of globalization and governance in the public sector. Written from the perspectives of both developed and developing countries, it uses governance and public administration interchangeably to argue that the tasks of implementation require the cooperation of both the public and private sectors, especially in a rapidly globalizing landscape. It then utilizes statistical analyses to investigate the challenges of globalization in managing human resources, ethics and accountability, sustainability, e-governances, and leadership in the public sector.